ANALISIS KUALITAS PELAYANAN SHOPEE DAN TOKOPEDIA MENGGUNAKAN METODE GAP ANALYSIS DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Dina lutfiana; Amri Yanuar; Febriani Sulistiyaningsih (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to find out (1) how is the quality of service provided by Shopee and Tokopedia, (2) the gap between the performance and expectations of Shopee and Tokopedia users on the quality of service of Shopee and Tokopedia, (3) what attributes are considered important by users Shopee and Tokopedia originating from Majalengka Regency are in accordance with the seven dimensions of SERVQUAL (4) proposed priority actions for what can be done to improve the quality of Shopee and Tokopedia services. This type of research is a quantitative research with a questionnaire method. The analysis used is Gap Analysis and Importance Performance Analysis (IPA). The calculation process uses SPSS version 23. The results of the study show that (1) seen from the difference test, the level of conformity analysis and the reality-expectation gap analysis based on the seven dimensions of SERVQUAL, the quality of Shopee and Tokopedia services is good in meeting the expectations of Shopee and Tokopedia users, (2 ) the average gap on Shopee's service quality attributes is negative except for the attributes on the dimensions of fulfillment, reliability, and contact. While all the attributes of Tokopedia's service quality are negative, (3) Based on the mapping on Shopee's service quality, there are 2 attributes that are considered important by Shopee users and need priority action. Whereas for the Tokopedia application, there are 3 attributes that are considered important, (4) evaluating and improving based on the mapping results through a Cartesian diagram on 2 Shopee attributes and 3 Tokopedia attributes that require priority action.